A method for producing a high-toughness aluminum alloy strip for a battery
Patent Information
- Application Number
- CN202611131634.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-10-23
AI Technical Summary
[0007]针对现有技术的不足,本发明提供了一种电池用高强韧铝合金带材轧制制备方法,解决了现有电池用铝合金带材在轧制过程中变形抗力大、无法兼顾高强度与高韧性,且常规冷却与润滑方式无法保障带材表面质量与内部组织均匀性的问题
1、本发明通过在线感应加热装置加热冷轧中间带材得到预热冷轧中间带材,配合单道次压下量控制轧机系统对预热冷轧中间带材进行轧制,加热冷轧中间带材使铝合金处于动态回复区,降低了预热冷轧中间带材的变形抗力,提高了预热冷轧中间带材的塑性;单道次压下量使预热冷轧中间带材内部产生深层剪切变形,细化了预热冷轧中间带材的晶粒组织,避免了严重加工硬化,兼顾了电池用高强韧铝合金带材的高强度与高韧性。
Smart Images

Figure CN122956192A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of aluminum alloy rolling processing technology, specifically to a method for rolling and preparing high-strength and high-toughness aluminum alloy strip for batteries. Background Technology
[0002] Aluminum alloy strip is widely used in the manufacture of battery casings and structural components for new energy vehicles. As the requirements for energy density and safety of power batteries continue to increase, aluminum alloy strip for batteries must possess both high strength and high toughness to prevent the battery casing from cracking under stress and deformation.
[0003] In conventional aluminum alloy processing, the main method to improve strip strength is to perform room temperature cold rolling on aluminum alloy ingots. Room temperature cold rolling causes work hardening within the strip, increasing its yield strength and tensile strength. However, as the amount of cold rolling deformation increases, the grains within the strip are elongated and broken, dislocation density increases, leading to a decrease in strip toughness and making the strip prone to cracking during stamping and forming processes.
[0004] Conventional processing methods typically involve an intermediate annealing process following the cold rolling step to eliminate work hardening. While intermediate annealing restores the plasticity and toughness of the aluminum alloy strip, it also eliminates cold-rolled dislocations, leading to a decrease in the strip's tensile strength. The conventional cold rolling followed by annealing method cannot simultaneously maintain both high strength and high toughness in the strip.
[0005] In aluminum alloy processing, conventional cold rolling uses room temperature rolling. At room temperature, the deformation resistance of intermediate aluminum alloy stock is high, requiring the rolling mill system to provide high reduction pressure. This high reduction pressure leads to increased heat generation in the metal deformation contact area, increasing the likelihood of uneven internal material microstructure distribution. Regarding lubrication and cooling technology, conventional rolling systems use traditional rolling oil to directly spray onto the contact area between the rolls and the metal stock. However, traditional spraying methods produce large droplets that cannot evenly cover the surface of the running strip.
[0006] In areas of high deformation, traditional rolling oil cannot maintain a continuous oil film in the high-pressure contact zone. Friction occurs between the metal and the work rolls, resulting in scratches, oxide patches, and localized roll sticking defects on the surface, thus compromising the integrity of the strip surface. Simultaneously, traditional lubrication systems lack protective gases and atomization control, leading to uneven cooling distribution and temperature variations across different parts of the strip. This affects the uniform distribution of the internal grain structure of the aluminum alloy strip, reducing the consistency of the finished product's processing quality. Summary of the Invention
[0007] To address the shortcomings of existing technologies, this invention provides a rolling preparation method for high-strength and high-toughness aluminum alloy strips for batteries. This method solves the problems of high deformation resistance, inability to balance high strength and high toughness, and inability of conventional cooling and lubrication methods to guarantee the surface quality and internal structure uniformity of the strips during the rolling process.
[0008] To achieve the above objectives, the present invention provides the following technical solution: This invention provides a method for rolling and preparing high-strength and high-toughness aluminum alloy strip for batteries, comprising the following steps: A composite warm rolling lubricant was prepared by mixing and stirring pentaerythritol tetranonanoate, zinc dialkyl dithiophosphate, tricresyl phosphate, isobutylene sulfide, ashless boronized polyisobutylene succinimide and isotridecyl alcohol polyoxyethylene ether. Aluminum alloy ingots are subjected to surface milling, annealing, hot rolling, and cold rolling to prepare cold-rolled intermediate strips. The cold-rolled intermediate strip is heated by an online induction heating device to prepare a preheated cold-rolled intermediate strip. The composite warm rolling lubricant and nitrogen are respectively introduced into the liquid phase channel and gas phase channel of the dual-fluid atomizing nozzle to form high-pressure hot nitrogen. The high-pressure hot nitrogen shears and atomizes the composite warm rolling lubricant, which is then sprayed onto the surface of the preheated cold-rolled intermediate strip and the surface of the mill work rolls. The mill system is controlled to roll the preheated cold-rolled intermediate strip to obtain aluminum alloy strip. The aluminum alloy strip is then wound up and cooled in air to prepare high-strength and high-toughness aluminum alloy strip for batteries.
[0009] By adopting the above technical solution, the use of a mixed-formulation composite warm rolling lubricant, combined with an online induction heating device to moderately heat the intermediate cold-rolled strip, and the use of high-pressure hot nitrogen gas formed by nitrogen and the composite warm rolling lubricant for shear atomization spraying, followed by single-pass large reduction rolling and air cooling, achieves the effects of reducing rolling deformation resistance, improving strip strength and toughness, and ensuring strip surface quality.
[0010] In the composite warm rolling lubricant, pentaerythritol tetranonanoate provides thermal stability, while zinc dialkyl dithiophosphate and tricresyl phosphate generate extreme pressure lubrication in the deformation zone. Sulfated isobutylene, ashless boronized polyisobutylene succinimide, and isomeric tridecyl alcohol polyoxyethylene ether work synergistically to form a uniform adsorption film on the strip and roll surfaces, reducing the coefficient of friction and deformation heat generation.
[0011] By using an online induction heating device to bring the cold-rolled intermediate strip to a predetermined temperature, the deformation resistance of the aluminum alloy is reduced, and the plasticity of the metal is improved. This promotes internal dislocation movement and dynamic recovery during subsequent large-reduction deformation, avoiding severe work hardening and preserving the toughness of the aluminum alloy strip.
[0012] Hot nitrogen, acting as a carrier gas, shears the lubricant into fine droplets in a two-fluid atomizing nozzle, uniformly adhering to the surface of the preheated cold-rolled intermediate strip and the mill work rolls. Nitrogen acts as an inert gas in the high-temperature deformation zone, reducing oxidation of the aluminum alloy surface. The uniformly distributed droplets spread rapidly under high temperature and pressure, maintaining the continuity of the oil film. Simultaneously, the large reduction in a single pass induces deep shear deformation within the strip, refining the grain structure and improving the strip's mechanical strength.
[0013] After rolling, the material is allowed to cool naturally in the air to release residual stress and solidify the grain structure, ultimately achieving a combination of high strength and high toughness.
[0014] Preferably, the composite warm rolling lubricant is made from the following raw materials in parts by weight: 100 parts by weight of pentaerythritol tetranonanoate; 0.5-1.2 parts by weight of zinc dialkyl dithiophosphate; 1.5-2.5 parts by weight of tricresyl phosphate; 0.2-0.6 parts by weight of sulfurized isobutylene; 0.3-0.8 parts by weight of ashless boronized polyisobutylene succinimide; and 0.1-0.3 parts by weight of isotridecyl alcohol polyoxyethylene ether. The specific method for preparing the composite warm rolling lubricant is as follows: the raw materials are put into a reactor equipped with a mechanical stirrer, and the reactor speed is controlled at 200-400 rpm at 25-35°C for stirring for 30-60 minutes.
[0015] By adopting the above technical solution, the limited lubricant formulation ratio ensures the synergistic efficiency between the base oil and the additives. Under the set reaction vessel temperature, speed and stirring time, the components are fully dispersed and mixed, preventing the additives from agglomerating or separating, and ensuring the fluidity and film-forming stability of the composite warm rolling lubricant in the two-fluid atomization process.
[0016] Preferably, the aluminum alloy ingot is selected from either 3003 aluminum alloy or 5052 aluminum alloy.
[0017] By adopting the above technical solutions, 3003 aluminum alloy and 5052 aluminum alloy have good basic mechanical properties and corrosion resistance. Combined with the preparation method of this invention, the interaction between precipitated phases and dislocations inside the alloy can be stimulated, which can meet the requirements of battery strip for strength and toughness.
[0018] Preferably, the face milling process involves placing the aluminum alloy ingot into a face milling machine for single-sided cutting, with a cutting thickness of 10-15 mm; the specific conditions for the annealing process are as follows: the aluminum alloy ingot that has undergone the face milling process is placed in an annealing furnace and annealed at 550-600°C for 12-24 hours.
[0019] By adopting the above technical solution, single-sided cutting with limited cutting thickness removes the segregation layer and crystallization defects on the surface of the ingot, providing a smooth initial surface; under the set high temperature and long-term annealing conditions, casting internal stress is eliminated, the internal composition of the alloy is homogenized, and the plasticity of hot deformation processing is improved.
[0020] Preferably, the hot rolling and cold rolling are specifically implemented as follows: the annealed aluminum alloy ingot is hot rolled to a thickness of 6.0-8.0 mm using a hot rolling mill to prepare a hot-rolled coil; the hot-rolled coil is cold rolled to a thickness of 2.0-3.0 mm in 1-3 passes at 20-30°C using a cold rolling mill to prepare the cold-rolled intermediate strip.
[0021] By adopting the above technical solution, hot rolling initially flattens and breaks up coarse grains in aluminum alloy ingots, followed by multiple passes of room temperature cold rolling to gradually accumulate deformation, providing a dense intermediate material with suitable thickness for subsequent online induction heating and warm rolling.
[0022] Preferably, by controlling the heating power and feeding speed of the online induction heating device, the body temperature of the cold-rolled intermediate strip reaches 160-190°C.
[0023] By adopting the above technical solution, the body temperature of the cold-rolled intermediate strip is limited to 160-190℃, so that the material is in the dynamic recovery zone, reducing the tendency to crack under large deformation conditions and improving the forming rate.
[0024] Preferably, the composite warm rolling lubricant is maintained at 25-35°C and introduced into the liquid phase channel of the dual-fluid atomizing nozzle, while the nitrogen gas heated to 120-140°C is introduced into the gas phase channel of the dual-fluid atomizing nozzle at a gauge pressure of 0.4-0.8 MPa.
[0025] By adopting the above technical solution, high-pressure hot nitrogen and room-temperature lubricating fluid interact within a set pressure range to ensure fine atomization particle size. At the same time, the heat energy carried by the carrier gas can increase the spreading rate of the lubricating fluid on the metal surface and maintain the activity of the oil film.
[0026] Preferably, the rolling mill system is controlled to apply a single pass reduction of 45% to 65% to the preheated cold-rolled intermediate strip for rolling, and the specific conditions for cooling in air are cooling to 20 to 30°C.
[0027] By adopting the above technical solution, a large reduction of 45% to 65% per pass achieves strong shear refinement of the internal structure of the material, and then cooling to room temperature solidifies the deformed structure, thus fully ensuring the final mechanical performance requirements of the strip.
[0028] This invention provides a method for rolling high-strength and high-toughness aluminum alloy strip for batteries. It has the following beneficial effects: 1. This invention obtains preheated cold-rolled intermediate strip by heating it with an online induction heating device, and then rolls the preheated cold-rolled intermediate strip using a single-pass reduction control mill system. Heating the cold-rolled intermediate strip puts the aluminum alloy in the dynamic recovery zone, reducing the deformation resistance of the preheated cold-rolled intermediate strip and improving its plasticity. The single-pass reduction causes deep shear deformation inside the preheated cold-rolled intermediate strip, refining the grain structure of the preheated cold-rolled intermediate strip, avoiding severe work hardening, and balancing the high strength and high toughness of the high-strength and high-toughness aluminum alloy strip for batteries.
[0029] 2. This invention prepares a composite warm rolling lubricant by mixing and stirring pentaerythritol tetranonanoate, zinc dialkyl dithiophosphate, tricresyl phosphate, sulfurized isobutylene, ashless borated polyisobutylene succinimide, and isomeric tridecanol polyoxyethylene ether. The composite warm rolling lubricant and nitrogen are introduced into a dual-fluid atomizing nozzle to form high-pressure hot nitrogen gas. The high-pressure hot nitrogen gas shears and atomizes the composite warm rolling lubricant, spraying it onto the surface of the preheated cold-rolled intermediate strip and the surface of the mill work rolls. The composite warm rolling lubricant forms an adsorption film on the surface of the preheated cold-rolled intermediate strip and the mill work rolls, reducing the coefficient of friction. The hot nitrogen gas acts as a carrier gas, shearing the composite warm rolling lubricant into fine droplets and ensuring that the droplets adhere evenly. The nitrogen gas plays a protective role in the high-temperature deformation zone, reducing oxidation on the surface of the preheated cold-rolled intermediate strip, maintaining the continuity of the oil film, and ensuring the surface quality of the high-strength and tough aluminum alloy strip for batteries.
[0030] 3. This invention prepares cold-rolled intermediate strip by milling, annealing, hot rolling, and cold rolling of aluminum alloy ingots. The rolled aluminum alloy strip is then coiled and cooled in air. Annealing eliminates the casting internal stress of the aluminum alloy ingot and homogenizes the internal composition of the aluminum alloy ingot. Hot rolling and cold rolling remove the coarse grains of the aluminum alloy ingot and provide a dense cold-rolled intermediate strip. Cooling in air releases residual stress and solidifies the grain structure of the aluminum alloy strip, ensuring the uniformity of the internal structure of the high-strength and tough aluminum alloy strip for batteries. Attached Figure Description
[0031] Figure 1 This is a scanning test image of the local roughness profile change on the surface of the rolling mill work roll according to the present invention; Figure 2 This is a test chart showing the continuous discharge temperature change monitoring during the rolling process of this invention; Figure 3 This is a test diagram of the engineering stress and engineering strain curves of the high-strength and high-toughness aluminum alloy strip for batteries of the present invention. Figure 4 This is a test diagram of the stamping load and stamping depth curve of the high-strength and tough aluminum alloy strip for batteries of the present invention. Detailed Implementation
[0032] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to test examples. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0033] Example 1: This example provides a method for rolling and preparing high-strength and high-toughness aluminum alloy strip for batteries, including the following steps: S1. 100 parts by weight of pentaerythritol tetranonanoate, 0.8 parts by weight of zinc dialkyl dithiophosphate, 2.0 parts by weight of tricresyl phosphate, 0.4 parts by weight of sulfurized isobutylene, 0.5 parts by weight of ashless boronized polyisobutylene succinimide, and 0.2 parts by weight of isotridecyl alcohol polyoxyethylene ether were added to a reactor equipped with a mechanical stirrer. The reactor speed was controlled at 300 rpm at 30°C and stirred for 45 min to prepare a composite warm rolling lubricant. S2. An aluminum alloy ingot (selected from 3003 aluminum alloy and 5052 aluminum alloy, 3003 aluminum alloy is selected in this embodiment) is placed in a face milling machine for single-sided milling with a thickness of 12mm. The 3003 aluminum alloy ingot after face milling is placed in an annealing furnace and annealed at 580℃ for 18 hours. The annealed 3003 aluminum alloy ingot is hot-rolled to a thickness of 7.0mm using a hot rolling mill to prepare a hot-rolled coil. The hot-rolled coil is then cold-rolled in two passes at 25℃ to a thickness of 2.5mm using a cold rolling mill to prepare a cold-rolled intermediate strip. S3. The cold-rolled intermediate strip is passed through an online induction heating device. The heating power and feeding speed of the online induction heating device are controlled to make the body temperature of the cold-rolled intermediate strip reach 175℃, thus obtaining a preheated cold-rolled intermediate strip. S4. The composite warm rolling lubricant is maintained at 30°C and fed into the liquid phase channel of the dual-fluid atomizing nozzle. Nitrogen gas is heated to 130°C and then introduced into the gas phase channel of the dual-fluid atomizing nozzle with a gauge pressure of 0.6MPa. The high-pressure hot nitrogen gas shears and atomizes the composite warm rolling lubricant. The sheared and atomized composite warm rolling lubricant is sprayed onto the surface of the preheated cold-rolled intermediate strip and the surface of the mill work rolls. The mill system is controlled to apply a single pass reduction of 55% to the preheated cold-rolled intermediate strip for rolling. The rolled aluminum alloy strip is coiled and cooled to 25°C in air to prepare a high-strength and high-toughness aluminum alloy strip for batteries.
[0034] Example 2: This example provides a method for rolling and preparing high-strength and high-toughness aluminum alloy strip for batteries, including the following steps: S1. 100 parts by weight of pentaerythritol tetranonanoate, 1.2 parts by weight of zinc dialkyl dithiophosphate, 2.5 parts by weight of tricresyl phosphate, 0.6 parts by weight of sulfurized isobutylene, 0.8 parts by weight of ashless boronized polyisobutylene succinimide, and 0.3 parts by weight of isotridecyl alcohol polyoxyethylene ether were added to a reactor equipped with a mechanical stirrer. The reactor speed was controlled at 400 rpm at 35°C and stirred for 60 min to prepare a composite warm rolling lubricant. S2. An aluminum alloy ingot (selected from 3003 aluminum alloy and 5052 aluminum alloy, 5052 aluminum alloy is selected in this embodiment) is placed in a face milling machine for single-sided milling with a thickness of 15mm. The 5052 aluminum alloy ingot after face milling is placed in an annealing furnace and annealed at 600℃ for 24 hours. The annealed 5052 aluminum alloy ingot is hot-rolled to a thickness of 8.0mm using a hot rolling mill to prepare a hot-rolled coil. The hot-rolled coil is then cold-rolled in three passes at 30℃ to a thickness of 3.0mm using a cold rolling mill to prepare a cold-rolled intermediate strip. S3. The cold-rolled intermediate strip is passed through an online induction heating device. The heating power and feeding speed of the online induction heating device are controlled to make the body temperature of the cold-rolled intermediate strip reach 190℃, thus obtaining a preheated cold-rolled intermediate strip. S4. The composite warm rolling lubricant is maintained at 35°C and fed into the liquid phase channel of the dual-fluid atomizing nozzle. Nitrogen gas is heated to 140°C and then introduced into the gas phase channel of the dual-fluid atomizing nozzle with a gauge pressure of 0.8MPa. The high-pressure hot nitrogen gas shears and atomizes the composite warm rolling lubricant. The sheared and atomized composite warm rolling lubricant is sprayed onto the surface of the preheated cold-rolled intermediate strip and the surface of the mill work rolls. The mill system is controlled to apply a single pass reduction of 65% to the preheated cold-rolled intermediate strip for rolling. The rolled aluminum alloy strip is coiled and cooled to 30°C in air to prepare a high-strength and high-toughness aluminum alloy strip for batteries.
[0035] Example 3: This example provides a method for rolling and preparing high-strength and high-toughness aluminum alloy strip for batteries, including the following steps: S1. 100 parts by weight of pentaerythritol tetranonanoate, 0.5 parts by weight of zinc dialkyl dithiophosphate, 1.5 parts by weight of tricresyl phosphate, 0.2 parts by weight of sulfurized isobutylene, 0.3 parts by weight of ashless boronized polyisobutylene succinimide, and 0.1 parts by weight of isotridecyl alcohol polyoxyethylene ether were added to a reactor equipped with a mechanical stirrer. The reactor speed was controlled at 200 rpm at 25°C and stirred for 30 min to prepare a composite warm rolling lubricant. S2. An aluminum alloy ingot (selected from 3003 aluminum alloy and 5052 aluminum alloy, 3003 aluminum alloy is selected in this embodiment) is placed in a face milling machine for single-sided milling with a thickness of 10mm. The 3003 aluminum alloy ingot after face milling is placed in an annealing furnace and annealed at 550℃ for 12 hours. The annealed 3003 aluminum alloy ingot is hot-rolled to a thickness of 6.0mm using a hot rolling mill to prepare a hot-rolled coil. The hot-rolled coil is then cold-rolled in one pass at 20℃ to a thickness of 2.0mm using a cold rolling mill to prepare a cold-rolled intermediate strip. S3. The cold-rolled intermediate strip is passed through an online induction heating device. The heating power and feeding speed of the online induction heating device are controlled to make the body temperature of the cold-rolled intermediate strip reach 160℃, thus obtaining a preheated cold-rolled intermediate strip. S4. The composite warm rolling lubricant is maintained at 25°C and fed into the liquid phase channel of the dual-fluid atomizing nozzle. Nitrogen gas is heated to 120°C and then introduced into the gas phase channel of the dual-fluid atomizing nozzle with a gauge pressure of 0.4MPa. The high-pressure hot nitrogen gas shears and atomizes the composite warm rolling lubricant. The sheared and atomized composite warm rolling lubricant is sprayed onto the surface of the preheated cold-rolled intermediate strip and the surface of the mill work rolls. The mill system is controlled to apply a single pass reduction of 45% to the preheated cold-rolled intermediate strip for rolling. The rolled aluminum alloy strip is coiled and cooled to 20°C in air to prepare a high-strength and high-toughness aluminum alloy strip for batteries.
[0036] Comparative Example 1: Compared with Example 1, the difference is that the gas-liquid two-phase spraying process in steps S1 and S4 is omitted, and the rolling and heat treatment process is replaced with the traditional cold rolling combined with static annealing. Specifically, steps S1 and S4 are omitted, and step S3 is replaced by continuing to cold roll the cold-rolled intermediate strip at 25°C using a cold rolling mill with a single pass of 55% reduction to prepare cold-rolled strip. The cold-rolled strip is then placed in an annealing furnace and statically annealed at 220°C for 2 hours to prepare high-strength and high-toughness aluminum alloy strip for batteries. All other aspects are the same.
[0037] Comparative Example 2: Compared with Example 1, the difference is that in step S4, high-pressure hot nitrogen is not used to shear and atomize the composite warm rolling lubricant. Instead, step S4 is replaced by: maintaining the composite warm rolling lubricant at 30°C and inputting it into the high-pressure liquid nozzle, using a liquid pressure of 0.6 MPa to spray the liquid composite warm rolling lubricant onto the surface of the preheated cold-rolled intermediate strip and the surface of the mill work rolls, controlling the mill system to apply a single pass of 55% reduction to the preheated cold-rolled intermediate strip for rolling, and then cooling the rolled aluminum alloy strip to 25°C in air to prepare a high-strength and high-toughness aluminum alloy strip for batteries. All other aspects are the same.
[0038] Comparative Example 3: Compared with Example 1, the difference is that in step S1, sulfurized isobutylene, ashless boronized polyisobutylene succinimide, and isomeric tridecyl alcohol polyoxyethylene ether were not added. Instead, step S1 was replaced by adding 100 parts by weight of pentaerythritol tetranonanoate, 0.8 parts by weight of zinc dialkyl dithiophosphate, and 2.0 parts by weight of tricresyl phosphate into a reactor equipped with a mechanical stirrer. The reactor speed was controlled at 300 rpm at 30°C and stirred for 45 min to prepare a composite warm rolling lubricant. All other steps were the same.
[0039] Test Example 1: Verify whether the high-pressure hot nitrogen shear atomization spraying process used in this invention can solve the surface thermal stress microcracks and roll sticking defects that occur during the large strain warm rolling of aluminum alloys.
[0040] The high-strength and high-toughness aluminum alloy strips for batteries prepared in Example 1 and Comparative Example 2, along with the corresponding rolling mill rolls, were used as test samples.
[0041] Microcrack detection on the surface of high-strength and high-toughness aluminum alloy strips for batteries was performed using dye penetrant testing. Under an ambient temperature of 25℃, dye penetrant testing agent was sprayed onto the surface of the strips. After a specified time, excess testing agent was removed, and a developer was applied. After development, the red development marks on the surface were observed visually under a white light source with the aid of a magnifying glass, and the number of developed cracks per square meter was counted.
[0042] The surface roughness change of the rolling mill work rolls was measured. Before the rolling process began, a portable surface roughness meter was used to select a measurement range on the surface of the rolling mill work rolls, and the transverse measurement position (mm) of the rolling mill work rolls was recorded. After rolling was completed and the rolling mill was stopped, the change in the surface profile height of the rolling mill work rolls at different transverse positions (μm) was obtained, and the increase in surface roughness was obtained by combining the results of the full-segment scanning test.
[0043] Assess the amount of aluminum powder adhering to the surface of the rolling mill work rolls. Take a specified mass of degreased cotton and wipe a fixed area along the axial direction on the surface of the rolling mill work rolls. Weigh and analyze the degreased cotton before and after wiping, calculate the mass of aluminum metal adhering to the unit area of the degreased cotton, and determine the amount of aluminum powder adhering.
[0044] Table 1. Test data on high-temperature rolled surface condition and anti-sticking roll performance of Example 1 and Comparative Example 2 Figure 1This is a scanning test image of the local roughness profile change of the mill work roll surface according to the present invention. The horizontal axis in the figure represents the transverse measurement position of the mill work roll (mm), and the vertical axis represents the change in the surface profile height of the mill work roll (μm). The curves in the figure represent the changes in the surface profile height of the mill work roll corresponding to Example 1 and Comparative Example 2, respectively.
[0045] Conclusion: Based on Table 1 and Figure 1 The data shows that the crack development quantity, surface roughness increase, and aluminum powder adhesion amount obtained in Example 1 are all lower than those in Comparative Example 2. Figure 1 Observations show that the fluctuation range of the roll profile height corresponding to Comparative Example 2 is much greater than that of Example 1.
[0046] Comparative Example 2 involved directly spraying a pure liquid composite warm rolling lubricant, maintained at 30°C, onto the surface of a preheated cold-rolled intermediate strip at 175°C. The pure liquid substance reacted violently with the high-temperature metal surface, inducing a dramatic temperature change on the surface of the preheated cold-rolled intermediate strip. This temperature gradient caused thermal stress within the metal material, inducing surface thermal stress microcracks.
[0047] Pure liquid substances in a boiling, vaporized state cannot establish a continuous and complete lubricating protective film in the rolling deformation zone. The failure of this protective film leads to direct contact and friction between the aluminum metal on the surface of the preheated, cold-rolled intermediate strip and the mill work rolls. The aluminum metal, under high temperature, undergoes plastic deformation under pressure and is forcibly adhered to and transferred to the surface of the mill work rolls, resulting in an increase in both the surface roughness and the amount of aluminum powder adhered in Comparative Example 2.
[0048] Example 1 utilizes high-pressure hot nitrogen gas heated to 130°C to shear and atomize a composite warm-rolling lubricant maintained at 30°C. The high-pressure hot nitrogen gas carries droplets of the composite warm-rolling lubricant, which are then sprayed onto the surface of the preheated cold-rolled intermediate strip and the surface of the mill work rolls. The gaseous substance acts as a heat conduction buffer between the gaseous substance and the high-temperature metal surface.
[0049] The buffer medium reduces the transient heat transfer rate of the liquid material in contact with the high-temperature metal surface, slowing down the temperature gradient of the surface layer of the preheated cold-rolled intermediate strip and preventing the formation of surface microcracks caused by thermal stress accumulation. The kinetic energy provided by the high-pressure airflow propels the atomized droplets to spread evenly and cover the surface of the deformation zone. Droplets containing extreme pressure additives such as zinc dialkyl dithiophosphate and tricresyl phosphate are excited by the extrusion friction heat, undergoing a tribochemical reaction to generate an inorganic extreme pressure reaction film at the metal contact interface. The inorganic extreme pressure reaction film forms an isolation barrier, blocking the adhesion and transfer path of aluminum metal inside the preheated cold-rolled intermediate strip to the roll surface, maintaining the original flatness of the mill work roll surface.
[0050] Test Example 2: Verify the thermodynamic control mechanism of gas-liquid two-phase atomized flow on preheated rolls in the rolling deformation zone, and prove that this scheme can provide a stable warm rolling environment.
[0051] The continuous rolling production line from Example 1 and Comparative Example 2 was selected as the test platform. A first non-contact infrared thermometer was vertically installed at the entrance of the preheated cold-rolled intermediate strip at the front end of the rolling mill system. A second non-contact infrared thermometer was vertically installed at the exit of the rolling deformation zone at the rear end of the rolling mill system.
[0052] Start the rolling equipment and control the sampling frequency of the non-contact infrared thermometer. The first non-contact infrared thermometer collects the inlet temperature of the preheated cold-rolled intermediate strip before it enters the roll contact interface in real time. Simultaneously, the second non-contact infrared thermometer collects the outlet temperature of the aluminum alloy strip after passing through the deformation zone following a single pass of 55% reduction rolling.
[0053] Record the temperature monitoring curve within the set continuous rolling time. Calculate the difference between the inlet temperature and outlet temperature at the same acquisition moment to obtain the temperature drop amplitude at that moment. Extract the highest and lowest outlet temperature values within the set time period and calculate the difference to obtain the outlet temperature fluctuation range.
[0054] Table 2. Dynamic heat exchange and temperature field stability test data of Example 1 and Comparative Example 2 Figure 2 This is a test chart for monitoring the continuous discharge temperature change during the rolling process of the present invention. The horizontal axis of the chart represents the continuous rolling time (s), and the vertical axis represents the discharge temperature value (°C). The curves in the chart represent the changes in discharge temperature values under different continuous rolling times for Example 1 and Comparative Example 2, respectively.
[0055] Conclusion: Based on Table 2 and Figure 2 The data shows that the temperature drop amplitude and the range of discharge temperature fluctuation obtained in Example 1 are both lower than those in Comparative Example 2. (Observation) Figure 2 It can be seen that the discharge temperature curve of Comparative Example 2 shows a large range of disordered oscillations during continuous rolling time, while the discharge temperature curve of Example 1 remains in a flat and extended state.
[0056] Comparative Example 2 involved directly spraying a pure liquid composite warm-rolling lubricant, maintained at 30°C, onto the surface of a preheated cold-rolled intermediate strip at 175°C. The single liquid substance boiled and vaporized upon contact with the high-temperature metal surface, absorbing and carrying away a large amount of ambient heat, causing a precipitous drop in the internal temperature of the preheated cold-rolled intermediate strip. The vapor bubbles generated by the boiling of the pure liquid phase were in a state of random collapse and recombination, resulting in uneven distribution of heat conduction rate within the deformation zone of the mill, causing significant fluctuations in the strip's exit temperature. The excessively large temperature drop deviated from the thermodynamic range required for large-strain processing of aluminum alloy materials, leading to an increase in the metal's internal deformation resistance.
[0057] In Example 1, a composite warm-rolling lubricant was maintained at 30°C and introduced into the liquid phase channel of a dual-fluid atomizing nozzle. Nitrogen gas was heated to 130°C and then introduced into the gas phase channel of the nozzle. The high-pressure hot nitrogen gas sheared and atomized the composite warm-rolling lubricant, forming a gas-liquid two-phase mixture. The high-pressure hot nitrogen gas at 130°C offset some of the heat absorbed by the droplet vaporization, thus preventing excessive heat loss from the preheated cold-rolled intermediate strip.
[0058] A gas-liquid two-phase mixture establishes a balance mechanism between heat input and heat output within the deformation zone of the rolling mill, simultaneously absorbing the mechanical frictional heat generated by the 55% reduction plastic deformation of the strip. High-pressure hot nitrogen gas carries droplets that are uniformly distributed on the surface of the preheated cold-rolled intermediate strip, maintaining a stable heat exchange rate at the metal interface. This constant heat exchange rate ensures that the exit temperature remains stable throughout the continuous rolling time, guaranteeing that the high-strength and high-toughness aluminum alloy strip for batteries completes its microstructure evolution process in a stable thermodynamic environment.
[0059] Test Example 3: Verify whether the strip prepared by the process and formula of this invention can overcome the defect of the inversion of strength and toughness in the traditional process in terms of mechanical properties, highlighting the advantages of this invention in the manufacture of high-strength and tough aluminum alloys for battery casings.
[0060] High-strength and high-toughness aluminum alloy strips for batteries prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were used as test samples. Samples were cut along the rolling direction of the high-strength and high-toughness aluminum alloy strips for batteries in an environment with a temperature of 25°C. The cut materials were then machined into standard tensile specimens.
[0061] Mount the standard tensile specimen in the upper and lower clamps of the universal testing machine. Adjust the initial clamp angle and spacing of the universal testing machine to ensure the standard tensile specimen is under vertical stress. Set the tensile rate of the universal testing machine and start the test program to apply an axial tensile load to the standard tensile specimen.
[0062] Record the force and displacement data during the tensile process until the standard tensile specimen breaks. Stop the universal testing machine and remove the broken standard tensile specimen. Process the collected data using the analysis software built into the universal testing machine, and read and record the corresponding yield strength, tensile strength, and elongation after fracture values of the standard tensile specimen.
[0063] Table 3. Room temperature tensile mechanical property test data of Examples 1 to 3 and Comparative Examples 1 to 3 Figure 3 This is a test graph of the engineering stress and engineering strain curves of the high-strength and high-toughness aluminum alloy strip for batteries of the present invention. The horizontal axis of the graph represents the engineering strain (%), and the vertical axis represents the engineering stress (MPa). The curves in the graph represent the changes in engineering stress and engineering strain of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 during the tensile test.
[0064] Conclusion: Based on Table 3 and Figure 3 The data show that the yield strength, tensile strength, and elongation after fracture test values of Examples 1 to 3 are all higher than those of Comparative Examples 1 to 3. The yield strength, tensile strength, and elongation after fracture test values of Example 1 are all higher than those of Comparative Examples 1, 2, and 3.
[0065] observe Figure 3 It can be seen that the engineering stress and strain curves of Example 1 have the widest range of extension during the plastic deformation stage, and fracture occurs the latest. Comparative Example 1 uses a conventional cold rolling combined with static annealing process. During the conventional cold rolling process, the metal grains are severely fragmented and elongated, leading to an exacerbation of work hardening. Although the subsequent static annealing process restores some plasticity, it also causes a decrease in dislocation density and grain growth. The cold rolling combined with static annealing process results in a state where the internal structure of the strip is characterized by coarse grains and residual stress, causing an inversion of metal strength and toughness, manifested as a simultaneous decrease in elongation after fracture and tensile strength.
[0066] Example 1 utilizes an online induction heating device to raise the temperature of the cold-rolled intermediate strip to 175°C, coupled with a single-pass reduction of 55%. The temperature and large-strain mechanical deformation create a coupling effect, inducing dynamic recovery within the aluminum matrix. This dynamic recovery consumes some of the deformation energy, slows down the work hardening rate, and promotes the formation of subgrain structures while retaining a high-density dislocation network. The fine, uniform subgrain structure and high-density dislocations jointly bear the external load during the tensile process, improving the overall tensile strength and elongation after fracture of the high-strength, high-toughness aluminum alloy strip for batteries.
[0067] Comparative Example 2: Pure liquid composite warm rolling lubricant was directly sprayed onto the surface of a preheated cold-rolled intermediate strip. The strip surface underwent severe thermal shock, resulting in microcrack defects. During the plastic deformation stage of the room-temperature tensile test, the surface microcracks acted as stress concentration sources. External loads drove the microcracks to propagate rapidly into the strip, causing premature fracture before reaching the theoretical deformation limit, resulting in a decrease in the elongation after fracture.
[0068] Comparative Example 3 did not contain 0.4 parts by weight of sulfurized isobutylene, 0.5 parts by weight of ashless boronized polyisobutylene succinimide, or 0.2 parts by weight of isomeric tridecyl alcohol polyoxyethylene ether. During the rolling process, the lubricant could not form an inorganic extreme pressure reaction film at the high-temperature and high-pressure interface. Local adhesion and tearing occurred at the metal interface, and scratches formed on the strip surface. These scratches also caused stress concentration under tensile stress, limiting the tensile deformation capacity of aluminum and resulting in lower mechanical property test values for Comparative Example 3.
[0069] Test Example 4: Verify the difference in deep drawing deformation capability between the strip prepared by this method and the strip prepared by the conventional method.
[0070] The high-strength and high-toughness aluminum alloy strips for batteries prepared in Examples 1, 1, and 3 were used as test samples. The high-strength and high-toughness aluminum alloy strips for batteries were processed into square sheet samples of specified dimensions using mechanical stamping equipment. Oil and impurities on the surface of the square sheet samples were cleaned.
[0071] Place the square sheet specimen flat between the blank holder and the base mold of the cupping tester. Activate the hydraulic clamping system of the cupping tester to apply a constant blank holder force to fix the square sheet specimen. Control the spherical punch of the specified diameter of the cupping tester to press the center of the square sheet specimen vertically at the set punching speed.
[0072] The surface condition of the deformed area of the square thin-sheet specimen is continuously monitored using a high-resolution camera system. When a penetrating crack appears on the surface of the square thin-sheet specimen, the advancement of the spherical punch is stopped. The displacement data of the spherical punch fed back by the testing system is recorded and extracted to obtain the corresponding stamping depth, i.e., the cupping value. The stamping load values throughout the entire stamping deformation process are recorded simultaneously.
[0073] Table 4. Test data on deep-drawing cupping performance of Example 1, Comparative Example 1 and Comparative Example 3 Figure 4 This is a test graph of the stamping load and stamping depth curve of the high-strength and tough aluminum alloy strip for batteries of the present invention. The horizontal axis of the graph represents the stamping depth (mm), and the vertical axis represents the stamping load (kN). The curves in the graph represent the changes in stamping load and stamping depth of Example 1, Comparative Example 1, and Comparative Example 3 during the cupping test.
[0074] Conclusion: Based on Table 4 and Figure 4 The data shows that the cupping value and maximum stamping load obtained in Example 1 are higher than those in Comparative Example 1 and Comparative Example 3. Example 1 maintained a wider deformation range during the stamping test, delaying the onset of penetrating cracks.
[0075] Comparative Example 1 omitted the gas-liquid two-phase spraying process and used conventional cold rolling combined with static annealing to prepare the strip. Conventional cold rolling led to an increase in internal dislocation density, and static annealing failed to completely eliminate the local residual stress accumulation caused by large deformation. This residual stress resulted in uneven grain slip resistance within the metal when the strip was subjected to bidirectional tensile stress from a spherical punch. This deformation inconsistency caused premature necking in weak areas, shortening the stamping depth and reducing the cupping value.
[0076] In the preparation of the composite warm rolling lubricant in Comparative Example 3, 0.4 parts by weight of sulfurized isobutylene, 0.5 parts by weight of ashless boronized polyisobutylene succinimide, and 0.2 parts by weight of isomeric tridecyl alcohol polyoxyethylene ether were not added. The liquid film layer lacking extreme pressure and dispersion components could not undergo sufficient tribochemical reaction in the contact area between the preheated cold-rolled intermediate strip and the mill work rolls. The rough peaks on the metal surface directly collided, generating mechanical scratches. Under the biaxial tensile load of the cupping test, these mechanical scratches evolved into stress concentration sources, inducing premature crack propagation and causing premature rupture of the square thin-sheet specimen.
[0077] Example 1 utilizes high-pressure hot nitrogen gas to shear and atomize a composite warm rolling lubricant, which is then sprayed onto the surface of a preheated cold-rolled intermediate strip. The formulation contains 100 parts by weight of pentaerythritol tetranonanoate, 0.8 parts by weight of zinc dialkyl dithiophosphate, 2.0 parts by weight of tricresyl phosphate, 0.4 parts by weight of sulfurized isobutylene, 0.5 parts by weight of ashless boronized polyisobutylene succinimide, and 0.2 parts by weight of isotridecyl alcohol polyoxyethylene ether.
[0078] Under conditions of 175℃ and high-pressure rolling, a gas-liquid two-phase mixture undergoes a tribochemical reaction to generate a continuous and uniform inorganic extreme pressure reactive film. This film seals surface defects, ensuring the integrity of the strip surface. Simultaneously, the thermo-coupling effect provides conditions for dynamic recovery, reducing localized stress concentration. The uniform internal structure and intact surface condition synergistically withstand the complex biaxial tensile loads in the cupping test, enhancing the plastic stamping deformation capability of the high-strength and high-toughness aluminum alloy strip for batteries.
Claims
1. A method for rolling and preparing high-strength and high-toughness aluminum alloy strip for batteries, characterized in that, Includes the following steps: A composite warm rolling lubricant was prepared by mixing and stirring pentaerythritol tetranonanoate, zinc dialkyl dithiophosphate, tricresyl phosphate, isobutylene sulfide, ashless boronized polyisobutylene succinimide and isotridecyl alcohol polyoxyethylene ether. Aluminum alloy ingots are subjected to surface milling, annealing, hot rolling, and cold rolling to prepare cold-rolled intermediate strips. The cold-rolled intermediate strip is heated by an online induction heating device to prepare a preheated cold-rolled intermediate strip. The composite warm rolling lubricant and nitrogen are respectively introduced into the liquid phase channel and gas phase channel of the dual-fluid atomizing nozzle to form high-pressure hot nitrogen. The high-pressure hot nitrogen shears and atomizes the composite warm rolling lubricant, which is then sprayed onto the surface of the preheated cold-rolled intermediate strip and the surface of the mill work rolls. The mill system is controlled to roll the preheated cold-rolled intermediate strip to obtain aluminum alloy strip. The aluminum alloy strip is then wound up and cooled in air to prepare high-strength and high-toughness aluminum alloy strip for batteries.
2. The method for rolling and preparing high-strength and high-toughness aluminum alloy strip for batteries according to claim 1, characterized in that, The composite warm rolling lubricant is made from the following raw materials in parts by weight: 100 parts by weight of pentaerythritol tetranonanoate; 0.5-1.2 parts by weight of zinc dialkyl dithiophosphate; Trimethylbenzene phosphate, 1.5-2.5 parts by weight; 0.2-0.6 parts by weight of sulfurized isobutylene; Ashless boronized polyisobutylene succinimide 0.3-0.8 parts by weight; 0.1-0.3 parts by weight of isomeric tridecyl alcohol polyoxyethylene ether.
3. The method for rolling and preparing high-strength and high-toughness aluminum alloy strip for batteries according to claim 2, characterized in that, The specific implementation method for preparing the composite warm rolling lubricant is as follows: The raw materials are put into a reactor equipped with a mechanical stirrer, and the reactor speed is controlled at 200-400 rpm at 25-35°C for 30-60 minutes.
4. The method for rolling and preparing high-strength and high-toughness aluminum alloy strip for batteries according to claim 1, characterized in that, The aluminum alloy ingot is selected from either 3003 aluminum alloy or 5052 aluminum alloy.
5. The method for rolling and preparing high-strength and high-toughness aluminum alloy strip for batteries according to claim 1, characterized in that, The face milling process involves placing the aluminum alloy ingot into a face milling machine for single-sided cutting, with a cutting thickness of 10-15 mm.
6. The method for rolling and preparing high-strength and high-toughness aluminum alloy strip for batteries according to claim 1, characterized in that, The specific conditions for the annealing process are as follows: the aluminum alloy ingot that has undergone the milling process is placed in an annealing furnace and annealed at 550-600°C for 12-24 hours.
7. The method for rolling and preparing high-strength and high-toughness aluminum alloy strip for batteries according to claim 1, characterized in that, The specific implementation methods of hot rolling and cold rolling are as follows: The annealed aluminum alloy ingot is hot-rolled to a thickness of 6.0-8.0 mm using a hot rolling mill to prepare hot-rolled coils. The hot-rolled coil is cold-rolled in 1 to 3 passes at 20 to 30°C to a thickness of 2.0 to 3.0 mm using a cold rolling mill to obtain the cold-rolled intermediate strip.
8. The method for rolling and preparing high-strength and high-toughness aluminum alloy strip for batteries according to claim 1, characterized in that, By controlling the heating power and feeding speed of the online induction heating device, the body temperature of the cold-rolled intermediate strip can reach 160-190℃.
9. The method for rolling and preparing high-strength and high-toughness aluminum alloy strip for batteries according to claim 1, characterized in that, The composite warm rolling lubricant is maintained at 25-35°C and introduced into the liquid phase channel of the dual-fluid atomizing nozzle, while the nitrogen gas heated to 120-140°C is introduced into the gas phase channel of the dual-fluid atomizing nozzle at a gauge pressure of 0.4-0.8 MPa.
10. The method for rolling and preparing high-strength and high-toughness aluminum alloy strip for batteries according to claim 1, characterized in that, The rolling mill system is controlled to apply a single-pass reduction of 45% to 65% to the preheated cold-rolled intermediate strip for rolling, and the specific conditions for cooling in air are cooling to 20 to 30°C.